Modulation of the fate of zein nanoparticles by their coating with a Gantrez® AN-thiamine polymer conjugate - Laura Inchaurraga; Ana L. Martínez-López; Muthanna Abdulkarim; Mark Gumbleton; Gemma Quincoces; Ivan Peñuelas; Nekane Martin-Arbella; Juan M. Irache (Elsevier, 2019)
The aim of this work was to evaluate the mucus-permeating properties of nanocarriers using zein nanoparticles (NPZ) coated with a Gantrez® AN-thiamine conjugate (GT). NPZ were coated by incubation at different GT-to-zein ratios: 2.5% coating with GT (GT-NPZ1), 5% (GT-NPZ2) and 10% (GT-NPZ3). During the process, the GT conjugate formed a polymer layer around the surface of zein nanoparticles. For GT-NPZ2, the thickness of this corona was estimated between 15 and 20 nm. These nanocarriers displayed a more negative zeta potential than uncoated NPZ. The diffusivity of nanoparticles was evaluated in pig intestinal mucus by multiple particle tracking analysis. GT-NPZ2 displayed a 28-fold higher diffusion coefficient within the mucus layer than NPZ particles. These results align with in vivo biodistribution studies in which NPZ displayed a localisation restricted to the mucus layer, whereas GT-NPZ2 were capable of reaching the intestinal epithelium. The gastro-intestinal transit of mucoadhesive (NPZ) and mucus-permeating nanoparticles (GT-NPZ2) was also found to be different. Thus, mucoadhesive nanoparticles displayed a significant accumulation in the stomach of animals, whereas mucus-penetrating nanoparticles appeared to exit the stomach more rapidly to access the small intestine of animals. Keywords: Zein, Nanoparticles, Thiamine, Oral delivery, Coating, Mucus permeating